Unveiling students’ conceptions of hydrostatic pressure: a cross-sectional analysis - Mohd Zaidi Amiruddin; Andi Suhandi; Nuzulira Janeusse Fratiwi; Nurdini Nurdini; Achmad Samsudin; Bayram Costu (Journal of Education and Learning (EduLearn), 2026)
This study investigates students’ conceptions of hydrostatic pressure, aiming to identify misconceptions (MC) and differences in understanding based on gender. A quantitative method with a cross-sectional study approach was used as the design in this study to explore and measure characteristics involving 186 students with an average age of 17-18 years from three provinces in Indonesia. Data were obtained using a Four-Tier Test to explore students’ scientific understanding, MC, and ignorance of hydrostatic pressure. A gender-based differential item functioning (DIF) analysis was also conducted to evaluate any potential bias in concept understanding between male and female students. The results showed that MC about factors affecting hydrostatic pressure were prevalent among students, for example: i) believing that hydrostatic pressure is independent of depth; ii) thinking that fluid type does not affect it; and iii) assuming that gravity has no impact. These findings highlight the need for targeted interventions to address these fundamental MC. DIF analysis showed a significant variation in understanding between genders, where male students tended to show better results on several aspects of scientific conceptions (SCs). These results highlight the necessity for mapping students’ initial conceptions before teaching, to enable the development of targeted instructional strategies aimed at addressing MC and improving understanding of critical physics concepts such as hydrostatic pressure.